Divided desire : restoring lost connections in the global village - Damara, Kenny (Eugene, Oregon : Resource Publications, 2013)
Can your ultimate desire ever be fulfilled? Everywhere you look, every time you listen, with each click and tap, there's something you desire. How do you know if what you desire will satisfy, or if you are seeing a "desire mirage"? The global village presents countless ways to connect to all kinds of information. We think we can scarcely live without these connections. Do we realize, however, that these connections often block or slow down connections to God, self, and others? Divided Desire is a journey along the road of desire--a road everyone travels. Along the journey, Kenny Damara explores why we desire what we desire in the global village today. What role does God have in fulfilling the ultimate desire of the heart? And how should we respond? -- Provided by publisher.
The Drama of Deception: What Good Desire is Not -- The Delight of Truth: What Good Desire Is -- The Characteristics of Our Culture -- Why Godlessness is the Desert of Desire -- Following Mirages in the Global Village -- Characteristics of Good Desire: Counter Global Village Culture -- Why Godliness in the Spring of Desire -- Drinking from the Streams of Godliness -- Our Ultimate Desire -- How Ultimate and Essential Desires are Fulfilled
Includes bibliographical references (pages 171-178).
Print version record.
Keywords: Christian life; Spiritual life -- Christianity; Desire -- Religious aspects; Christian life; Desire -- Religious aspects; Spiritual life -- Christianity; RELIGION / Christian Life / General; Electronic books